Maya the Bee 2: The Honey Games ([United States] : Shout Factory, 2018)
When a tribute announcement demanding half the hives honey threatens the very survival of the hive, Maya and her sidekick Willy defy the queens orders and go to Buzztropolis to confront the Empress. The Empress invites them to participate in the Honey Games; however, she explains that if they win, all is forgiven, but if they lose, she will take all of the summer honey.